Cryopreservation-induced proteomic alterations in Pêga donkey (Equus asinus) spermatozoa - Camilo Jose Ramirez-Lopez; Isabella Cristina Tolêdo Alves Costa; Wassali Valadares de Sousa; Yara Martins da Silva; Faider Alberto Castano Villadiego; Tayna Bolsam da Silva; Renner Philipe Rodrigues Carvalho; Arabela Guedes de Azevedo Viana; Jose Carlos Montes-Vergara; Mariana Machado-Neves; Simone Eliza Facioni Guimaraes; Fabio Cesar Sousa Nogueira; et al. (Cryobiology, 2026)

Molecular architectures of self-assembling peptides for combating resistant bacteria - Cesar Augusto Roque-Borda; Waleska Stephanie da Cruz Nizer; Subham Kumar Vishwakarma; Oswaldo Julio Ramirez Delgado; Zidane Qriouet; Andréia B. Meneguin; Fernando Rogério Pavan (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Evaluation of suspended particles in a tropical coral reef system using the backscatter intensity signal of an ADCP - Cesar Linton-Izquierdo; David Salas-Monreal; Gabriela Athie; José Antolín Ake-Castillo; Mark Marin-Hernandez; Rocío de Guadalupe Bernal-Ramirez; José de Jesús Salas-Perez (Marine Pollution Bulletin, 2026)

Detrital zircon geochronology of the Jurassic strata in the Santander-Floresta Massif, Colombia: Constraints on the provenance and its tectonic implication - Giovanny Jiménez; Carlos Alberto García Ramirez; Mauro Cesar Geraldes (Journal of South American Earth Sciences, 2025)

Improving Patient Awareness on Breast Cancer Radiotherapy Side Effects and Survivorship: A Patient Education Intervention at the Mays Cancer Center - Jiwon Park; Shriya L. Veluri; Joshua Asper; Cesar Ramirez; Isabella Mata; Amy Le; Shraddha M. Dalwadi (Journal of Cancer Education, 2025)

Toxicity of six representative polycyclic aromatic compounds in five marine test species - Benjamin P. de Jourdan; David L. Daniel; Piero R. Gardinali; Cesar Ramirez; Chris J. Langdon; Emily Stefansson; Thomas F. Parkerton; William A. Stubblefield (Science of The Total Environment, 2025)

Stability of five strains of PRRSV in tap water at different temperatures - Valeria Lugo-Mesa; Nader M. Sobhy; Muhammad Luqman; Christian D. Ramirez-Camba; Cesar A. Corzo; Sagar M. Goyal (Veterinary Microbiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Tilapia Skin Extracted Collagen, PLA, Genipin Crosslinking and Electrospinning Technique for Tissue Engineering Membranes Elaboration - Jesús Manuel Quiroz-Castillo; Abraham Alejandro Leyva-Verduzco; Lerma Hanaiy Chan-Chan; Claudia Georgina Ramirez-Mendoza; Celia Olivia García-Sifuentes; Julio Cesar Zamorano-Apodaca; María Mónica Castillo-Ortega; Diana Carolina González-González; Dora Evelia Rodríguez Félix (Journal of Aquatic Food Product Technology, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

An imperative for soil spectroscopic modelling is to think global but fit local with transfer learning - Raphael A. Viscarra Rossel; Zefang Shen; Leonardo Ramirez Lopez; Thorsten Behrens; Zhou Shi; Johanna Wetterlind; Kenneth A. Sudduth; Bo Stenberg; Cesar Guerrero; Asa Gholizadeh; Eyal Ben-Dor; Mervin St Luce; et al. (Earth-Science Reviews, 2024)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Sources, Characteristics, and Therapeutic Applications of Mesenchymal Cells in Tissue Engineering - Rosa Angelica Gonzalez-Vilchis; Angelica Piedra-Ramirez; Carlos Cesar Patiño-Morales; Concepcion Sanchez-Gomez; Nohra E. Beltran-Vargas (Tissue Engineering and Regenerative Medicine, 2022)

Chemical profiles of cannabis sativa medicinal oil using different extraction and concentration methods - Cesar N. Pegoraro; Diego Nutter; Mario Thevenon; Cristina L. Ramirez (Natural Product Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Productive behavior in growing kid goats and methane production with the inclusion of chokecherry leaf (Prunus salicifolia) - Lizbeth E. Robles Jimenez; Jose A. Ruiz Perez; Di Lorenzo Nicolas; Alfonso J. Chay Canul; Julio Cesar Ramirez-Rivera; Daniela Villegas-Estrada; Einar Vargas-Bello-Pérez; Manuel Gonzalez-Ronquillo (Tropical Animal Health and Production, 2020)

Environmental Levels, Sources, and Cancer Risk Assessment of PAHs Associated with PM2.5 and TSP in Monterrey Metropolitan Area - Francisco E. Longoria-Rodríguez; Lucy T. González; Alberto Mendoza; Cesar Leyva-Porras; Alejandro Arizpe-Zapata; Miguel Esneider-Alcalá; Karim Acuña-Askar; Octavio Gaspar-Ramirez; Olivia López-Ayala; Juan M. Alfaro-Barbosa; Oxana V. Kharissova (Archives of Environmental Contamination and Toxicology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Spatial estimation of surface ozone concentrations in Quito Ecuador with remote sensing data, air pollution measurements and meteorological variables - Cesar I. Alvarez-Mendoza; Ana Teodoro; Lenin Ramirez-Cando (Environmental Monitoring and Assessment, 2019)

Individual differences in blink rate modulate the effect of instrumental control on subsequent Pavlovian responding - Catherine A. Hartley; Cesar A. O. Coelho; Emily Boeke; Franchesca Ramirez; Elizabeth A. Phelps (Psychopharmacology, 2019)

Fractionation of Dissolved Organic Matter by Co-Precipitation with Iron: Effects of Composition - Yingxun Du; Cesar E. Ramirez; Rudolf Jaffé (Environmental Processes, 2018)

Impact of Diet on Breast Cancer Risk: A Review of Experimental and Observational Studies - Laura Vera-Ramirez; M. Carmen Ramirez-Tortosa; Pedro Sanchez-Rovira; Cesar L. Ramirez-Tortosa; Sergio Granados-Principal; Jose A. Lorente; Jose L. Quiles (Critical Reviews in Food Science and Nutrition, 2013)